Apalancamiento financiero y su impacto sobre la rentabilidad, en la producción agricola-cultivo de banano- cantón Pasaje 2022. - Tenecela Tocto, Kristel Solange; Palacios Correa, Yuleise Estefania (Machala : Universidad Técnica de Machala, 2024)
The study focuses on the analysis of the levels of financial leverage in companies dedicated to the cultivation of bananas and plantains in 2022, using a positivist quantitative approach and a non-experimental design. Data from 25 companies obtained from the SUPERCIAS platform were used and they were classified as SMEs. The quantitative epistemological approach is based on the idea that events in the world follow measurable patterns, using tools such as measurement, experimentation, and statistical analysis. A positivist paradigm is adopted to confirm hypotheses using statistical methods. The hypothetico-deductive method is used to formulate and test theories, with phases of logical deduction and empirical verification. A descriptive methodology is used to provide a complete representation of the reality studied. The non-experimental design observes phenomena without altering variables, and an observation instrument is used to collect data through direct observation. The data was collected from the financial statements of the companies through the platform of the Superintendency of Securities and Insurance Companies, using the financial leverage formula for the analysis in conjunction with the profitability ratios. Reflecting that debt levels directly impact profitability, companies with a heavier financial burden tend to have lower profitability, suggesting that excess leverage may limit profit generation in the agricultural sector. However, financial leverage can be beneficial if managed properly. Although it can contribute positively to profitability, it is crucial to exercise caution in its application. The importance of efficient financial management strategies to optimize the use of leverage is highlighted, highlighting the need for prudent and strategic financial management that considers both the risks and benefits associated with leverage.
El estudio se centra en el análisis de los niveles de apalancamiento financiero en empresas dedicadas al cultivo de banano y plátano en el año 2022, utilizando un enfoque cuantitativo positivista y un diseño no experimental. Se emplearon datos de 25 empresas obtenidos de la plataforma SUPERCIAS y se clasificaron como pymes. El enfoque epistemológico cuantitativo se basa en la idea de que los sucesos del mundo siguen patrones medibles, utilizando herramientas como la medición, la experimentación y el análisis estadístico. Se adopta un paradigma positivista para confirmar hipótesis usando métodos estadísticos. El método hipotético-deductivo se emplea para formular y probar teorías, con fases de deducción lógica y verificación empírica. Se utiliza una metodología descriptiva para proporcionar una representación completa de la realidad estudiada. El diseño no experimental observa fenómenos sin alterar variables, y se emplea un instrumento de observación para recopilar datos mediante la observación directa. Los datos se recolectaron de los estados financieros de las empresas mediante la plataforma de la Superintendencia de Compañías Valores y Seguros, utilizando la fórmula del apalancamiento financiero para el análisis en conjunto con las ratios de rentabilidad. Reflejando que los niveles de endeudamiento impactan directamente en la rentabilidad, las empresas con una carga financiera más pesada tienden a tener una rentabilidad menor, sugiriendo que el exceso de apalancamiento puede limitar la generación de beneficios en el sector agrícola. Sin embargo, el apalancamiento financiero puede ser beneficioso si se gestiona adecuadamente. Aunque puede contribuir positivamente a la rentabilidad, es crucial ejercer prudencia en su aplicación. Se subraya la importancia de estrategias de gestión financiera eficientes para optimizar el uso del apalancamiento, destacando la necesidad de una gestión financiera prudente y estratégica que considere tanto los riesgos como los beneficios asociados con el apalancamiento.
Keywords: APALANCAMIENTO FINANCIERO; RENTABILIDAD; AGRICOLA; PYMES